How do you simplify #sqrt(4x^5)-xsqrt(x^3)#?

2 Answers
Aug 3, 2016

Answer:

#sqrt (x^5)#

Explanation:

#sqrt(4x^5)-x sqrt(x^3) ?#

#sqrt(2^2*x^4*x)-x sqrt(x^2*x)#

#2x^2sqrt(x)-x*x sqrt x#

#2x^2 sqrt x-x^2sqrt x#

#x^2 sqrt x(2-1)#

#x^2 sqrt x*1#

#x^2 sqrt x#

#"Or ;"#

#sqrt(x^4*x)#

#sqrt (x^5)#

Aug 3, 2016

Answer:

#sqrt(4x^5)-xsqrt(x^3)=x^2sqrtx#

Explanation:

#sqrt(4x^5)-xsqrt(x^3)#

= #sqrt(2xx2xx x xx x xx x xx x xx x)-xsqrt(x xx x xx x)#

= #sqrt(ul(2xx2)xx ul(x xx x) xx ul(x xx x) xx x)-xsqrt(ul(x xx x) xx x)#

= #2x^2sqrtx-x xx x sqrtx#

= #2x^2sqrtx-x^2sqrtx#

= #x^2sqrtx#